1998
DOI: 10.1152/ajpcell.1998.275.2.c527
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-activated protein kinase expression and activation in smooth muscle

Abstract: There is relatively little known about expression and activation of p38 mitogen-activated protein kinases (MAPKs) through G protein-linked, seven-transmembrane-spanning (STM) receptors in mammalian smooth muscle. To investigate the role of p38 MAPK in smooth muscle, we cloned and sequenced the p38 MAPK expressed in canine smooth muscles. A full-length clone of the canine p38 MAPK expressed in colonic smooth muscle was obtained by RT-PCR. The deduced amino acid sequence revealed 99% identity to the human p38 MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
35
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 26 publications
10
35
0
Order By: Relevance
“…In addition, the mechanisms of p38MAPK activation differed between agonists, with NA having a requirement for calcium but not herbimycin A-sensitive tyrosine kinases and with ET-1 being partially dependent on extracellular calcium and tyrosine kinases. Identification of 4 p38MAPK isoforms in rat mesenteric small arteries confirms and extends the observations of Hedges et al, 19 who identified p38␣ in canine smooth muscle. The present study shows GPCR activation of p38␣ and/or p38␤ isoforms in smooth muscle, with no detectable activation of the SAPK3/p38␥ or SAPK4/p38␦ isoforms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the mechanisms of p38MAPK activation differed between agonists, with NA having a requirement for calcium but not herbimycin A-sensitive tyrosine kinases and with ET-1 being partially dependent on extracellular calcium and tyrosine kinases. Identification of 4 p38MAPK isoforms in rat mesenteric small arteries confirms and extends the observations of Hedges et al, 19 who identified p38␣ in canine smooth muscle. The present study shows GPCR activation of p38␣ and/or p38␤ isoforms in smooth muscle, with no detectable activation of the SAPK3/p38␥ or SAPK4/p38␦ isoforms.…”
Section: Discussionsupporting
confidence: 87%
“…The p38␣/␤ band had an apparent molecular mass of 41 kDa, in agreement with canine smooth muscle p38MAPK. 19 The molecular mass of SAPK3 (p38␥) and SAPK4 (p38␦) was Ϸ39 kDa. …”
mentioning
confidence: 97%
“…Recent publications showed that bradykinin and thromboxane A 2 activate MAPK pathways via PKC-dependent G i ␣ protein coupling in human cells (20,29). In addition, PKC may increase the contractility of the airway smooth muscle by inhibiting caldesmon (via the MAPK pathways) and calponin (directly), which are involved in modulation of the actin-myosin interaction (30,61). We show here that blockage of PKC by calphostin C effectively inhibits fenoterol-induced sensitization.…”
Section: Discussionmentioning
confidence: 55%
“…Recent studies underline the role of the MAPK in the intracellular processes of airway smooth muscle proliferation and sensitization (2,30,32,46,58,61 (12,23,32,53). Moreover, MAPK increases the G i protein activity, which results in a functional uncoupling between G s protein and ␤ 2 -adrenoceptor (2,32,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation